2021
DOI: 10.1177/2325967121989678
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Radiographic, and Arthroscopic Outcomes of Surgical Repair for Radial and Avulsed Lesions on the Lateral Meniscus Posterior Root During ACL Reconstruction: A Systematic Review

Abstract: Background: Clinical outcomes of surgical repairs for tears of the lateral meniscus posterior root (LMPR) in patients undergoing anterior cruciate ligament (ACL) reconstruction (ACLR) have not been comprehensively investigated. Purpose: To systematically review the clinical, radiographic, and arthroscopic results of surgical repairs for tears of the LMPR in patients undergoing ACLR. Study Design: Systematic review; Level of evidence, 4. Methods: A systematic electronic search of the PubMed and Embase databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 33 publications
3
30
1
2
Order By: Relevance
“…For example, after medial meniscus repair, MRI evaluation has demonstrated continued meniscus extrusion [ 24 ] and low healing rates [ 25 ]. Similarly, the paucity of research regarding the clinical implications of PRTs of the lateral meniscus demonstrates lax healing of up to 21% [ 26 ], and a recent systematic review was unable to conclude whether root repair restored the functional hoop stress characteristics required of the meniscus to distribute compression forces across the knee evenly [ 27 ]. Furthermore, a recent study found characteristic clinical differences between the medial and lateral meniscus PRTs, including the association of trauma in lateral meniscus PRTs, and older age and higher grade of OA changes of the knee in medial meniscus PRTs [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, after medial meniscus repair, MRI evaluation has demonstrated continued meniscus extrusion [ 24 ] and low healing rates [ 25 ]. Similarly, the paucity of research regarding the clinical implications of PRTs of the lateral meniscus demonstrates lax healing of up to 21% [ 26 ], and a recent systematic review was unable to conclude whether root repair restored the functional hoop stress characteristics required of the meniscus to distribute compression forces across the knee evenly [ 27 ]. Furthermore, a recent study found characteristic clinical differences between the medial and lateral meniscus PRTs, including the association of trauma in lateral meniscus PRTs, and older age and higher grade of OA changes of the knee in medial meniscus PRTs [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…A level 4 systematic review of 9 nonrandomized studies with 215 patients reported favorable functional outcome after combined ACLR and LMPRT repair with a meniscus healing rate >90%. 42 However, in a long-term study, Shelbourne et al 34 reported that subjective outcomes were not significantly different in patients whose LMPRT was left untreated compared with a matched control group with intact menisci. The mean IKDC score after 10 years was 84.6 ± 14 in the LMPRT group.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, we have excluded those with a partial tear or healing tear at the time of arthroscopy, which led to the limited sample size. A recent systematic review about “clinical outcomes of surgical repairs for LMPR tears in patients undergoing ACLR” published by Zheng T et al [ 43 ] contained 9 studies with a total of 215 knees only (mean = 19.5, range = 8–41). The present study’s sample size is still larger than the mean of the reported studies.…”
Section: Discussionmentioning
confidence: 99%